Heavy Metal Pollution From Illegal Mining ‘Galamsey’ Activities on the Viability of Clarias gariepinus in the Oda River, Ghana - Seth Adusei; Emmanuel Kwesi Arthur; Emmanuel Gikunoo; William Amponsah; Frank Ofori Agyemang; Godfred Ohemeng‐Boahen (Aquaculture, Fish and Fisheries)
ABSTRACT Activities associated with illegal mining, ‘galamsey’, often result in significant environmental degradation, particularly to water bodies. In the case of River Oda, like all other affected areas in Ghana, galamsey operations contribute to the pollution of the water body with some heavy metals such as mercury (Hg), cadmium (Cd) and arsenic (As). These heavy metals have posed a significant threat to the aquatic environment (fish population) and human health. In this study, the effect of the concentration of Hg, Cd and As at varying concentrations (2, 4 and 6 ppm) and its interactions on the growth and survival of Clarias gariepinus fingerlings was investigated. A total of 154 C. gariepinus fingerlings were exposed to varying concentrations of the heavy metals for 42 days. The results revealed that Hg exhibited a negative effect on fish survival, whereas Cd showed a positive impact, with varying patterns of growth and mortality rates within the three concentrations. As, however, showed no significant effect on the growth and survival of fingerlings. Combinations of Hg, Cd and As concentrations resulted in a significant negative effect on fish growth and survival. Furthermore, the interactions between Hg and Cd, as well as Hg and As, had negative significant impacts on the fingerlings, with higher concentrations resulting in lower growth and survival rates. Cd and As had a positive effect on the fingerlings. The study concluded that a higher concentration of Hg, with or without the presence of other heavy metals, may result in the high reduction of growth and survival of fish. This research highlights the environmental risks of continuous Hg, Cd and As release into the River Oda, emphasizing the need for monitoring and control to protect ecosystems, human well‐being and local economies as called for in Sustainable Development Goal 6.